Swimsuit styles and detail preferences of selected female Kamia hall residents - Jaurigue, Reden B
This study is about determining the preferred swimsuit style and detail p[references of selected female residents of Kamia Hall. The objectives of the study were to: identify and describe the swimsuit style and detail preferences of the Kamia respondents; determine the factors and influences that are considered most important in swimsuit selection; and determine from the preference analysis whether the respondents' tastes in swimwear is conservative or fashionable. Fifty respondents were selected from the 212 total population of Kamia Hall by convenience sampling because sampling criterion set in the study states that qualified respondents must own at least a pair of swimsuit. Main findings are as follows: the preferred type of swimsuit is one-piece swimsuits. For the respondents who prefer one-piece swimsuits, their preference is for maillot. For two-piece preference, it was found out that the preferences depend on the suit bottom which is boyleg. The neckline style most preferred is the low cut. They also prefer the bikini cut for swimsuit legs and the preferred swimsuit back depth is mid-scoop. The preferred type of fabrics for swimsuits is medium-weight. Th re respondents prefer pink, peach, white and yellow for light colors, while black, green, and blue for dark colors. The factor given top priority by the respondents in choosing their swimsuits is fit; followed by: comfort, appearance, style, quality, price, durability, suitability, and prestige. Other considerations that the respondents consider while choosing swimsuits are the opinions of other people and the stress that may be directed at them. The respondents consider media (printed or TV) of the most influence while friends and peers are a close second. The respondents prefer styles that cover sensitive body areas but are lenient with coverage of non-erogenous body parts like neck, back, and legs. Therefore, it can be said that the preferences are conservative to begin with but has an eye for fashion.